Exploring Conversational and Physiological Aspects of Psychotherapy Talk - Avdi, Evrinomy; Evans, Chris (Frontiers in Psychology, 2020)
This study is part of a larger exploration of ‘talk and cure’ that combines the examination of talk-in-interaction, with nonverbal displays, and measurements of the client’s and therapist’s autonomic arousal during therapy sessions. A key assumption of the study is that psychotherapy entails processes of intersubjective meaning-making that occur across different modalities and take place in both verbal/explicit and nonverbal/implicit domains. A single session of a psychodynamic psychotherapy is analysed with a focus on the expression and management of affect, with an aim to describe key interactive events that promote change in both semantic and procedural domains. The clinical dialogue is analysed discursively, with a focus on the conversational processes through which new meanings are jointly constructed and affective states shared; detailed attention is paid to nonverbal displays of affiliation and affect. Furthermore, we explore whether the interactional patterns implicated in joint meaning-making, as revealed by analysing the therapeutic conversation, have correlates in the autonomic arousal of the two protagonists, as reflected in their heart rates. Conversation analysis has still untapped potential to illuminate interactional patterns that underlie the practice of psychotherapy. In this exploratory study we suggest that discursive analyses of talk-in-interaction can be enriched through detailed focus on nonverbal displays as well as measures of physiological arousal. Drawing upon the analysis, we suggest that bringing the methodological strengths of language-based analysis into fertile dialogue with embodied quantitative data can help our explorations of what’s really going on in psychotherapy.